Cryptography in coherent optical information networks using dissipative metamaterial gates - Xomalis, Angelos (2019)
All-optical encryption of information in fibre telecommunication networks offers lower complexity and far higher data rates than electronic encryption can deliver. However, existing optical layer encryption methods, which are compatible with keys of unlimited length, are based on nonlinear processes that require intense optical fields. Here, we introduce an optical layer secure communication protocol that does not rely on nonlinear optical processes but instead uses energy redistribution of coherent optical waves interacting on a plasmonic metamaterial absorber. We implement the protocol in a telecommunication optical fibre information network, where signal and key distribution lines use a common coherent information carrier. We investigate and demonstrate different encryption modes, including a scheme providing perfect secrecy. All-optical cryptography, as demonstrated here, exploits signal processing mechanisms that can satisfy optical telecom data rate requirements in any current or next-generation frequency band with bandwidth exceeding 100 THz and a switching energy of a few photons per bit. This is the first demonstration of an optical telecommunications application of metamaterial technology.